Analisis Retorika Pada Pidato Presiden Jokowi “Bersatu Menghadapi Corona” Sebagai Himbauan Melalui Media Youtube - Faza Fat Han Fadhillah; Irwansyah Irwansyah (JURNAL LENSA MUTIARA KOMUNIKASI, 2021)
During this COVID-19 pandemic, many people were confused about how to deal with COVID-19. In dealing with this, President Joko Widodo made a virtual speech to deal with this pandemic in order to prevent the spread of the COVID-19 virus. Based on this background, this study will discuss the meaning of the rhetorical study from President Jokowi, which contains an appeal to continue to live the days according to the Covid 19 protocol. This research was conducted with a qualitative approach and used descriptive analysis methods, which provide an overview and understanding to the reader about Aristotle's rhetorical theory in the art of persuasion carried out by President Jokowi through a press release on "Together Against Corona." with literature studies that already exist in previous research. The formulation of the problem that the researcher raises is how the analysis of the content of President Jokowi's speech "United Facing Corona" delivered through a youtube video intersects with ethos, logos, pathos as dimensions of rhetoric or its aspects. This research shows that President Jokowi, who acts as a communicator in this speech in persuading the public, has fulfilled ethos, logos, and pathos when viewed from Aristotle's art of persuasion. The speech "United Facing Corona" applies the use of five aspects in rhetoric, such as the discovery aspect, the regulatory aspect, the style aspect, the delivery aspect, the memory aspect, and others. The speech "United Facing Corona" as a whole has shown the rhetorical concept of Aristotle.